Sosialisasi Pendidikan Berbasis Kearifan Lokal kepada Masyarakat Desa Girimakmur Kecamatan Malangbong - Asyari, Lutfi; Gunawan, Dani; Adiredja, Rajji Koswara; Ramdan, Mohamad (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to provide insight into knowledge about education through local cultural wisdom in Girimakmur Village, Malangbong District, by providing insight into knowledge about the importance of education from elementary to secondary education. Problems that arise in these areas are resolved in three stages of activity, namely preparation, implementation and evaluation. The results of community service activities show the level of success with an indication of the similar mindset of educators in the Malangbong District environment, there is a positive response from service participants related to an understanding of education that must synergize with the local life of the local area and most people have understood the concept of developing local culture which can be used as as an icon of community development